From Big to Small Cities: A Qualitative Analysis of the Causes and Outcomes of Post‐Recession Municipal Bankruptcies. (29th October 2019) - Davidson, Mark
Abstract: Two cities loom large in the history of American urban restructuring. New York City's 1975 technical bankruptcy and Detroit's 2013 Chapter 9 bankruptcy have played an oversized role in urban theory. This is currently reflected in competing theories of post‐recession urban restructuring. "Austerity urbanism" uses Detroit as an exemplar, whereas "pragmatic municipalism" adopts the converse position arguing post‐recession reform is defined by local context. This paper draws on the small cities literature to generate a different account of recent municipal bankruptcies and their broader impacts. It uses qualitative methods to survey the causes and outcomes of all eight post‐recession Chapter 9 bankruptcies. The research recognizes the potential nationwide significance of these extreme events but avoids focusing on big city examples. The paper's findings suggest small and medium sized cities play a significant role in shaping recession‐related restructuring.